Graphene–Graphene Interactions: Friction, Superlubricity, and Exfoliation. Issue 13 (13th February 2018) - Sinclair, Robert C.; Suter, James L.; Coveney, Peter V.
Abstract: Graphite's lubricating properties due to the "weak" interactions between individual layers have long been known. However, these interactions are not weak enough to allow graphite to readily exfoliate into graphene on a large scale. Separating graphite layers down to a single sheet is an intense area of research as scientists attempt to utilize graphene's superlative properties. The exfoliation and processing of layered materials is governed by the friction between layers. Friction on the macroscale can be intuitively understood, but there is little understanding of the mechanisms involved in nanolayered materials. Using molecular dynamics and a new forcefield, graphene's unusual behavior in a superlubric state is examined, and the energy dissipated between two such surfaces sliding past each other is shown. The dependence of friction on temperature and surface roughness is described, and agreement with experiment is reported. The accuracy of the simulated behavior enables the processes that drive exfoliation of graphite into individual graphene sheets to be described. Taking into account the friction between layers, a peeling mechanism of exfoliation is predicted to be of lower energy cost than shearing. Abstract : Graphite's lubricating properties due to the "weak" interactions between individual layers, have long been known. However, graphene still cannot be exfoliated on a large scale. A new classical molecular dynamics forcefield is applied to unravel the remarkable interactions between graphene sheets. It is found that peeling graphene sheets apart, rather than shearing, is an easier route to exfoliation.